Software engineering a practitioner's approach - Pressman, Roger S. (McGraw-Hill series in computer science, 2000)
For almost three decades, Roger Pressman's Software Engineering: A Practitioner's Approach has been the world's leading textbook in software engineering. The new eighth edition represents a major restructuring and update of previous editions, solidifying the book's position as the most comprehensive guide to this important subject. The eighth edition of Software Engineering: A Practitioner's Approach has been designed to consolidate and restructure the content introduced over the past two editions of the book. The chapter structure will return to a more linear presentation of software engineering topics with a direct emphasis on the major activities that are part of a generic software process. Content will focus on widely used software engineering methods and will de-emphasize or completely eliminate discussion of secondary methods, tools and techniques. The intent is to provide a more targeted, prescriptive, and focused approach, while attempting to maintain SEPA's reputation as a comprehensive guide to software engineering. The 39 chapters of the eighth edition are organized into five parts - Process, Modeling, Quality Management, Managing Software Projects, and Advanced Topics. The book has been revised and restructured to improve pedagogical flow and emphasize new and important software engineering processes and practices